1996
DOI: 10.1183/09031936.96.09020307
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized BAL fluid proteins in patients with interstitial lung diseases

Abstract: Oxygen-derived free radicals, released by phagocytic cells, have been postulated to contribute to lung tissue damage. We therefore investigated oxidative damage to proteins from bronchoalveolar lavage fluid (BALF) as an indicator of oxidative stress and to assess antioxidant defences in the lungs.We examined BAL fluids from patients with interstitial lung diseases, such as idiopathic pulmonary fibrosis (IPF, nonsmokers (NS) and smokers (S)), sarcoidosis (SARC, nonsmokers), and asbestosis (ASB, ex-smokers (EXS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
78
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 36 publications
0
78
0
Order By: Relevance
“…Oxidative modification of mitochondrial DNA has been observed in lung epithelial cells of IPF patients [5]. Oxidised BALF proteins, characterised by oxidation of methionine residues or carbonylation, are increased in patients with IPF [6,7]. There is also an increase in 8-isoprostane, a biomarker of oxidative stress, in the BALF of IPF patients [8].…”
mentioning
confidence: 72%
“…Oxidative modification of mitochondrial DNA has been observed in lung epithelial cells of IPF patients [5]. Oxidised BALF proteins, characterised by oxidation of methionine residues or carbonylation, are increased in patients with IPF [6,7]. There is also an increase in 8-isoprostane, a biomarker of oxidative stress, in the BALF of IPF patients [8].…”
mentioning
confidence: 72%
“…The role of ROS in the development of lung fibrosis has already been reported in a large number of pathological conditions, such as bronchopulmonary dysplasia in pre-term infants [20], adult respiratory distress syndrome [21,22], sarcoidosis [23], idiopathic pulmonary fibrosis [24], and in the animal models of silicosis and asbestos-induced pulmonary fibrosis [25,26]. The most relevant model demonstrating the role of ROS in lung fibrosis is certainly the murine model of lung fibrosis induced by intratracheal instillation of bleomycin.…”
Section: Discussionmentioning
confidence: 99%
“…2 Either directly or via formation of intermediate lipid or protein peroxidation products, they may enhance inflammation by activation of stress kinases and redox-sensitive transcription factors such as NF-kappa B and AP-1. 3 Previously, it was shown that reactive oxygen species such as superoxide, hydrogen peroxide, and hydroxyl radicals contribute to inflammatory injury in adult patients with asthma, 4,5 chronic bronchitis, 6 interstitial lung disease (ILD), 7 or cystic fibrosis. 8 High levels of free radicals are produced in the lungs by activated inflammatory cells, i.e., neutrophils, eosinophils, and alveolar macrophages.…”
Section: Introductionmentioning
confidence: 99%